55 successful Harvard Law School application essays : what worked for them can help you get into the law school of your choice / Print book
Competition has never been more intense for admittance into the nation's top law schools. The application essay represents your only chance to plea your case to admissions officers. Why select you over so many other qualified applicants? Your essay needs to do more than simply list your background and accomplishments. It must reveal the depth of your passion for law, the discipline you bring to this demanding profession, and the strength of character you possess for the ethical and moral challenges that lie ahead. Learn by example. Harvard Law School is one of the premier law schools in America. Every year, thousands of elite applicants try for a few hundred slots. Of the dedicated few accepted, fifty-five have shared the application essays that helped them make the cut. * Learn what works. * Structure your essay for maximum impact. * Avoid common pitalls. Each essay is analyzed by the staff of the Harvard Crimson, Harvard's daily newspaper, and accompanied by no-nonsense advice on crafting your own. 55 Successful Harvard Law School Application Essays will give you all the help you need to write the essay that will get you in.